2020
DOI: 10.1111/trf.15711
|View full text |Cite
|
Sign up to set email alerts
|

Increased collection efficiency of CD34+ cells after mobilization with preemptive use of plerixafor followed by leukocytapheresis on the same day

Abstract: BACKGROUND Plerixafor should be administered 6 to 11 hours before starting leukocytapheresis. However, we have been using plerixafor followed by leukocytapheresis according to different time schedules since 2007. Our objective was to compare the CD34+ cell collection efficiency (CE1) of the first leukocytapheresis performed after using plerixafor at different time intervals. STUDY DESIGN AND METHODS Same‐day schedule refers to the administration of plerixafor at 10:00 AM and starting the leukocytapheresis on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Thus, a CD34+ cell count can be performed in the morning, administering plerixafor if the count is poor and performing an apheresis session in the afternoon of the same day. Our group found that in autologous donors, CD34+ cell collection efficiency of same-day processes was higher when compared with next-day apheresis [58]. A Dutch group has shown a good correlation between data obtained with a fully automated haematology analyser and CD34+ cell count by flow cytometry.…”
Section: How Is Plerixafor Used? Dosing and Administrationmentioning
confidence: 64%
“…Thus, a CD34+ cell count can be performed in the morning, administering plerixafor if the count is poor and performing an apheresis session in the afternoon of the same day. Our group found that in autologous donors, CD34+ cell collection efficiency of same-day processes was higher when compared with next-day apheresis [58]. A Dutch group has shown a good correlation between data obtained with a fully automated haematology analyser and CD34+ cell count by flow cytometry.…”
Section: How Is Plerixafor Used? Dosing and Administrationmentioning
confidence: 64%
“…One recent study has shown that the efficacy is higher if apheresis was performed on the same day as the administration of plerixafor. 40 However, there are limited studies regarding the effect of plerixafor on the kinetics of stem cell mobilization.…”
Section: Use Of Plerixafor For Autologous Sctmentioning
confidence: 99%
“…reported an approximately seven-fold increase in circulating CD34+ cells after 6 hours of plerixafor injection (22). In a study conducted in 2020, a comparison between apheresis products of two groups with 6-hour intervals and 14 to 20-hours intervals indicated higher stem cell dose in the first group (23). A study on sickle cell disease patients illustrated a peak above 80 CD34+/µL in two to three hours after drug administration (24).…”
Section: Discussionmentioning
confidence: 99%